Effect of Extract of Nerium oleander L. Leaves and Proline Acid on Growth and Yield of Chict (Cicer aeitium L.) - Ahmed, Sanaa A. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
stract The experiment aimed to study the effect of different concentrations (10 and 20)% of Nerium oleander L. leaves extract and proline (20 and 30) ppm on growth and yield of Cicer aeitium L. The field experiment was conducted during the growth season of 2012-2013. The results showed that the best concentration of N. oleander extract leaves was 10% that showed significant increasing in plant height, branches and leaves number and dry weight during first and second periods measurement as well as the chlorophyll containing in leaves , crop growth ratio (CGR), number of pods, weight of 100 seeds, percentage of seed carbohydrates. The results revealed that two concentrations of proline (20 and 30) ppm showed a significant increase in the chlorophyll contained in leaves, number of pods comparing with control plant , but the same concentrations led to significant decrease in dry weight and CGR .